TERAPI MUSIK RELIGI TERHADAP TINGKAT STRES PADA LANSIA DI UPT PSTW KASIAN JEMBER - Marwah; Eka Fitriyah Ladjiru (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
Elderly is someone who has entered the age of 60 years and over. Problems that often occur in the elderly one of which is stress. Stress is a universal phenomenon that occurs in everyday life and can not be avoided and will be experienced by everyone. Non-pharmacological action to deal with stress is to provide classical religious music therapy. This therapy is very easy to do and has no harmful side effects. Mozart effect is one of the terms for the effects that can be produced by a music that can improve one's intelligence. The purpose of this study was to analyze the effect of classical religious music therapy on stress levels in the elderly at UPT PSTW Kaisian Jember. The instruments used were questionnaire sheets and Standard Operating Procedures as a measurement tool. This therapy is carried out within 30 minutes for one day. The research method used was Quasi one group pre-test post-test design experiment. The population is 70 respondents and the sample is 41 respondents. The sampling technique used is simple random sampling. Data analysis used Wilcoxon signed rank test with a 0.05 degree of error. The results obtained 0,000 <α which means that there is an influence of classical religious music therapy on stress levels in the elderly at UPT PSTW Kasian Jember, with data of 17.10% of the elderly experiencing moderate stress levels, 26.80% of the elderly experiencing mild stress levels, and 56, 10% of elderly experience normal stress. It is recommended in this study is to apply religious music therapy to reduce the occurrence of stress in the elderly